The BASES Expert Statement on emotion regulation in sport - Lane, A. M.; Beedie, C. J.; Jones, M. V.; Uphill, M.; Devonport, T. J. (Journal of Sports Sciences, 2012)
Emotions experienced before and during sports competition have been found to influence sports performance. Emotion regulation is defined as the automatic or deliberate use of strategies to initiate, maintain, modify or display emotions (Gross & Thompson, 2007) and is proposed to occur when a discrepancy exists between current and desired emotions. Two distinct motivations to regulate emotion - hedonic and instrumental (in short, for pleasure or for purpose) - have been proposed (Tamir, 2009). The instrumental approach might provide a more fruitful area of investigation for sports researchers as some athletes hold beliefs that supposedly pleasant emotions such as happiness and calmness associate with poor performance and supposedly unpleasant emotions such as anxiety and anger associate with good performance (Hanin, 2010). Athletes are more likely to try to regulate an emotion if they believe that doing so will facilitate performance. Strategies that encourage re-appraisal of factors that trigger emotions are proposed to be preferable. In this British Association of Sport and Exercise Sciences (BASES) expert statement, a summary of the key theoretical issues are offered leading to evidence-based recommendations for practitioners and researchers.